O sacrifício de Cristo como superação do sacrifício antigo - Godoy, Edevilson de (2009)
This study examines the sacrifice of Christ as a conquest of ancient sacrifice, from the paradigm of victimizing mechanism explained by Franco-American anthropologist René Girard. The thesis affront the theme of sacrifice in perspective Girard, highlighting the evolution of his thought: from the mimetic process that culminates in the classic concept of the scapegoat as exorcism of community violence, it reaches a more dialectic, in which maintaining the archaic theory, highlights the Christian message of sacrifice as gift of self for the life of another. The research fits into the context of studies on the role of religion in human relations, that is, the phenomenon of religion in community relations, to, from Girard, focusing on the "sacrifice of Christ as the greatest expression of love of history able to redeem sinful man. The study has a humble ambition to show the extraordinary contribution of theory Girard theology. It presents an overall discussion of the thought of Girard. Keep is the dogmatic biblical field, including the possibility of the compatibility between Catholic theology and thought Girard at a specific point and absolutely qualifying: the word sacrifice can be perfectly applied to the event of Christ's passion